Antimicrobial resistance of Escherichia coli and associated factors in pet dogs from Cajamarca city (Peru). - Gamarra-Ramírez, R. (2025)
The inherent susceptibility of dogs to multiple bacterial infections, combined with inadequate management of antibacterial agents, represents significant public and veterinary health concerns. This study aimed to determine the prevalence of resistance in Escherichia coli isolates to commonly used antibacterials and identify associated resistance factors in pet dogs from Cajamarca city. One hundred fecal samples were collected, from which E. coli strains were cultured and isolated. Antibiogram testing was conducted using the Kirby-Bauer method. Simultaneously, a survey was administered to the owners of the sampled animals to identify risk factors. One hundred percent of the isolates were resistant to at least one antibacterial agent. The prevalence of resistance to streptomycin [STR] (61 %) and ampicillin [AMP] (53 %) was categorized as "very high". In comparison, resistance to cephalexin [CEP] (47 %), sulfamethoxazole/trimethoprim [SXT] (41 %), gentamicin [GEN] (40 %), and tetracycline [TET] (33 %) was categorized as "high", and resistance to enrofloxacin [ENR] (10 %) was classified as "low". Resistance to STR was associated with age, while resistance to SXT was associated with sex and cohabitation with other animal species (p < 0.05). The risk of acquiring STR resistance in E. coli was higher in adult dogs than in younger ones (OR 2.304 [95 % CI: 1.012-5.244], p = 0.047). Regarding SXT, the likelihood of E. coli acquiring resistance in females was higher than in males (OR 3.987 [95 % CI: 1.672-9.088], p = 0.002), and cohabitation with other animal species was also a risk factor (OR 3.468 [95 % CI: 1.258-9.562], p = 0.016).